2018
DOI: 10.1021/acs.inorgchem.7b03272
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure and High Temperature Synthesis of the Iron Pernitride FeN2

Abstract: The high pressure chemistry of transition metals and nitrogen was recently discovered to be richer than previously thought, due to the synthesis of several transition metal pernitrides. Here, we explore the pressure-temperature domain of iron with an excess of nitrogen up to 91 GPa and 2200 K. Above 72 GPa and 2200 K, the iron pernitride FeN is produced in a laser-heated diamond anvil cell. This iron-nitrogen compound is the first with a N/Fe ratio greater than 1. The FeN samples were characterized from the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 53 publications
6
69
1
Order By: Relevance
“…[19,20] These peaks are indexed to the orthorhombic symmetry, although a few unidentified peaks remain. The obtained Miller indices and axial ratios are consistent with those of so-far-reported marcasite-type transition metal pernitrides (FeN 2 , [14,15] CoN 2 , [13] OsN 2 , [21] RuN 2 , [22] and RhN 2 [23] ). On the other hand, the arsenopyrite-type structure is also suggested as plausible crystal structure for the late transition metal pernitrides because the arsenopyrite-type structure (monoclinic) is formed via a small distortion from the marcasite-type one (orthorhombic) and the difference of the formation enthalpy between these structures is likely small.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…[19,20] These peaks are indexed to the orthorhombic symmetry, although a few unidentified peaks remain. The obtained Miller indices and axial ratios are consistent with those of so-far-reported marcasite-type transition metal pernitrides (FeN 2 , [14,15] CoN 2 , [13] OsN 2 , [21] RuN 2 , [22] and RhN 2 [23] ). On the other hand, the arsenopyrite-type structure is also suggested as plausible crystal structure for the late transition metal pernitrides because the arsenopyrite-type structure (monoclinic) is formed via a small distortion from the marcasite-type one (orthorhombic) and the difference of the formation enthalpy between these structures is likely small.…”
Section: Resultssupporting
confidence: 86%
“…It is found that the c-and a-axes are the most compressible and incompressible axes, respectively. The order of axial compressibility ( a = 4.4 × 10 -3 GPa -1 , b = 5.3 × 10 -3 GPa -1 , and c = 7.8 × 10 -3 GPa -1 for the a-, b-, and c-axes, respectively) is consistent with that of the other transition-metal marcasite-type pernitrides (FeN 2 , [14,15] CoN 2 , [13] RuN 2 , [22] and RhN 2 [23] ). The experimentally determined K 0 of marcasite-type pernitrides are reported for RhN 2 [K 0 = 235 (13) GPa], [23] CoN 2 [K 0 = 223 (5) GPa], [13] and FeN 2 [K 0 = 250 (16) GPa, 344(13) GPa], [14,15] and OsN 2 (K 0 = 358 GPa).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations